Dakwah dan Filantropi: Jalan Menuju Kesejahteraan Ummat - Muhammad Jaelan Arifin; Pediati, Lia; Muhammad Fadly Alifi (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study examines philanthropic da'wah as an effective strategy in realizing the welfare of Muslims. The method used is a descriptive qualitative approach by relying on literature studies and relevant secondary data, including documents, previous research, and statistical data on the potential of zakat and philanthropy in Indonesia. The analysis is carried out systematically by connecting empirical data and theories of Islamic da'wah and philanthropy to understand the role of philanthropic da'wah in increasing social awareness and economic empowerment of the people. The results of the study show that philanthropic da'wah not only functions as a dissemination of religious values, but also as a social movement that optimizes the potential of zakat, infaq, and sedekah to reduce poverty and increase social solidarity. This study emphasizes the importance of strengthening philanthropic institutions, transparency in fund management, and collaboration between various parties to achieve sustainable impacts. Thus, philanthropic da'wah can be a strategic path in building a more just, independent, and prosperous society socially and economically.